Assessing Gait After Changing Prosthetic Foot: Contribution of Subjective and Objective Measurements. A Pilot Study. Issue 2 (April 2021) - Gouteron, Anaïs; Casillas, Jean-Marie; Calistri, Laurine; Morisset, Claire; Laroche, Davy; Gueugnon, Mathieu
ABSTRACT: Introduction: Although the choice of a prosthetic foot is crucial for the locomotion of individuals with limb loss, it partly reposes on the subjective perception of the patient without evaluating systematically the objective foot performance in gait laboratory. However, it is still unclear whether subjective perception is sufficient to evaluate foot performance and if it is in accordance with objective foot performance during gait. Materials and Methods: We aimed to address these questions by asking five unilateral transtibial prosthesis users to rate their habitual energy-storage-and-return foot (ESAR foot) and a new ESAR foot and to perform a three-dimensional gait analysis with each foot. Results: Our results revealed that perception is globally associated with objective gait performance. More specifically, gait stability seems to be the most relevant parameter for patient perception. Conclusions: This pilot study highlights the value of the subjective perception for the fitting of a prosthetic foot and suggests that pooling together subjective and objective evaluations provides substantial benefit.